Determinants and Potential of Indonesia’s Frozen Shrimp Exports - Vela Rostwentivaivi; Rita Nurmalina; Harmini; Netti Tinaprilia (Economics Development Analysis Journal, 2025)
This study examines the main factors influencing the flow of Indonesian frozen shrimp exports and explores opportunities to strengthen trade with key destination countries. The research uses a panel data regression approach, including estimation and potential analysis, focusing on 12 major trading partners from 2012 to 2023. The study analyzes frozen shrimp under HS code 030617, one of Indonesia's leading fishery export commodities. The findings show that importer gross domestic product, importer population, and revealed comparative advantage positively influence frozen shrimp exports. In contrast, Indonesia's gross domestic product, economic distance, and non-tariff barriers have a negative impact. Based on the regression results, the potential analysis identifies several countries with strong export prospects, including Australia, the Netherlands, Hong Kong, the United Kingdom, Japan, Germany, Canada, South Korea, Malaysia, France, and Singapore. These results provide meaningful managerial implications, such as increasing domestic production capacity, enhancing export competitiveness, and developing focused marketing strategies to penetrate high-potential markets.